2021
DOI: 10.1096/fj.202002531r
|View full text |Cite
|
Sign up to set email alerts
|

Changes in brown adipose tissue lipid mediator signatures with aging, obesity, and DHA supplementation in female mice

Abstract: Brown adipose tissue (BAT) dysfunction in aging and obesity has been related to chronic unresolved inflammation, which could be mediated by an impaired production of specialized proresolving lipid mediators (SPMs), such as Lipoxins-LXs, Resolvins-Rvs, Protectins-PDs, and Maresins-MaRs. Our aim was to characterize the changes in BAT SPMs signatures and their association with BAT dysfunction during aging, especially under obesogenic conditions, and their modulation by a docosahexaenoic acid (DHA)-rich diet. Lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 107 publications
3
20
0
Order By: Relevance
“…As described in previous studies of our group, no significant changes were observed in BW or fat mass after long-term DHA supplementation and/or physical exercise [ 39 , 40 ]. In addition, no significant differences were observed between groups regarding absolute and relative lean mass.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…As described in previous studies of our group, no significant changes were observed in BW or fat mass after long-term DHA supplementation and/or physical exercise [ 39 , 40 ]. In addition, no significant differences were observed between groups regarding absolute and relative lean mass.…”
Section: Resultssupporting
confidence: 67%
“…In this respect, we have recently reported that a 16-week resistance training (RT) program (alone or in combination with Docosahexaenoic acid (DHA)) improved the lower and upper limb muscle strength and quality in overweight/obese postmenopausal women [ 38 ]. Moreover, recent studies of our group in aged and obese mice have shown that DHA and/or treadmill training can delay the progression of non-alcoholic fatty liver disease and inflammation [ 39 ] and that long-term DHA supplementation was able to reduce inflammation in the dysfunctional brown adipose tissue (BAT), as well as the alteration in lipid metabolism biomarkers (total and LDL-cholesterol) that characterizes aging and obesity in mice [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed the enhancement of the expression of browning genes in subcutaneous WAT and thermogenic genes in BAT. Félix-Soriano et al [ 15 ] discovered that a high-fat diet with DHA supplementation restored UCP1 expression in BAT. Lynes et al [ 16 ] observed that the level 12,13-diHOME was elevated in the plasma of humans and mice exposed to cold.…”
Section: Discussionmentioning
confidence: 99%
“…This lower activity of BAT is related to a higher susceptibility of suffering obesity and type 2 DM and an increase of BAT activity has been suggested as a possible therapeutic strategy against obesity due to its thermogenic function [ 58 , 60 ]. We have recently reported a reduced iBAT activity in aged CT mice that was aggravated in aged DIO mice [ 61 ]. The various factors contributing to the loss of BAT with age have not been yet established [ 62 ].…”
Section: Discussionmentioning
confidence: 99%